Reframing Islamic Education Governance Through a Socio-Cultural Perspective: Lessons from Spain and Indonesia - Rizal Anshorudin; Mohamad Erihadiana; Ilham Nurjaman; Dede Supriyatna (UIN Sunan Gunung Djati Bandung, 2025)
Islamic education evolves within diverse socio-cultural and political contexts in Muslim-majority and Muslim-minority countries, directly affecting its governance, legitimacy, and sustainability. These differences generate structural challenges related to secularism, religious identity, and state involvement in Islamic education. This study aims to analyze and compare the governance of Islamic education in Spain and Indonesia from a socio-cultural perspective. The research employed a Systematic Literature Review (SLR) following the PRISMA 2020 framework and the PISCo approach, synthesizing 18 Scopus-indexed scholarly and Google Scholar articles. The findings indicate that Islamic education in Spain operates under a top-down and formal-legal governance system, strongly shaped by secularism and the minority status of Muslims, resulting in institutional constraints and persistent Islamophobia. In contrast, Islamic education in Indonesia develops through a plural and community-based governance model that integrates religious values with local culture in a Muslim-majority society. This study implies that sustainable Islamic education requires inclusive, contextual, and participatory governance models capable of addressing socio-cultural diversity while promoting religious moderation and social cohesion.